2022
DOI: 10.1108/ijchm-09-2021-1101
|View full text |Cite
|
Sign up to set email alerts
|

Luxury hotels as orchestrators in gastronomic destination development and management: the case of Borgo Egnazia and the Itria Valley

Abstract: Purpose The aim of this paper is to uncover the main capabilities that a luxury hotel needs to develop when functioning as the orchestrator of a local gastronomic business ecosystem. Design/methodology/approach Given the limited attention previous literature has placed on the role of luxury hotels as orchestrators in luxury gastronomic business ecosystems, this paper adopts a qualitative approach, i.e. the exploratory analysis of a single case study: the Italian high-end hotel Borgo Egnazia. Findings The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 89 publications
0
8
0
Order By: Relevance
“…Lastly, the "wellness experiencescapes" that emerge from this study both define and characterize the formulas of experiential value that foresee a variety of touchpoints requiring creative partnerships among the different actors (Ferraris et al, 2021). These would form constellations of local actors in which Spa Retreat facilities would act as hubs (Franco et al, 2022).…”
Section: Theoretical Implicationsmentioning
confidence: 90%
See 1 more Smart Citation
“…Lastly, the "wellness experiencescapes" that emerge from this study both define and characterize the formulas of experiential value that foresee a variety of touchpoints requiring creative partnerships among the different actors (Ferraris et al, 2021). These would form constellations of local actors in which Spa Retreat facilities would act as hubs (Franco et al, 2022).…”
Section: Theoretical Implicationsmentioning
confidence: 90%
“…, 2021). These would form constellations of local actors in which Spa Retreat facilities would act as hubs (Franco et al. , 2022).…”
Section: Discussionmentioning
confidence: 99%
“…According to previous research, food creates a tourism attraction focused on culinary traditions embedded in local identity (Ueda & Poulain, 2021), which also becomes sophisticated when marketed as part of a luxury experience (Park et al, 2021). The role of luxury hotels in the development of local gastronomy is vital for the creation of relationships between local stakeholders and the promotion of a destination through the tradition of local products (Franco et al, 2022). In this sense, previous research has also identified ‘art’ as a source of luxury (see Miller, 2016), which is especially manifested in the menus of celebrity chefs and their Michelin starred restaurants (De Albuquerque Meneguel et al, 2019).…”
Section: The Links Between Luxury and Gastronomy In Digital Tourism M...mentioning
confidence: 99%
“…This study aims to fill this gap and contribute to the scholarly understanding of the digital promotion of gastronomic experiences in a luxury setting. Luxury hotels were selected in this study because of their role in the protection and promotion of the gastronomic features of a destination (Franco et al, 2022). Luxury hotels focus on luxury food marketing because luxury‐dining options are part of the general features of luxury hotels and, also, because of the power of personalization of gastronomic experiences (Campbell, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The authors find that the perception towards the Republic of Tatarstan changed through the cooking class, resulting in a stronger desire to visit that region. Franco et al (2022) have conducted an exploratory analysis of high-end hotel (Borgo Egnazia) located in Apulia, Italy. Building on interviews with several stakeholders in the town where the hotel is located (Fasano), the authors suggest that luxury hotels in some cases can function as coordinators of a local gastronomic business ecosystem.…”
Section: Value and Image Of Gastronomy Experiences By Restaurants And...mentioning
confidence: 99%